2020
DOI: 10.1371/journal.ppat.1008933
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial effector protein prevents MAPK-mediated phosphorylation of SGT1 to suppress plant immunity

Abstract: Nucleotide-binding domain and leucine-rich repeat-containing (NLR) proteins function as sensors that perceive pathogen molecules and activate immunity. In plants, the accumulation and activation of NLRs is regulated by SUPPRESSOR OF G2 ALLELE OF skp1 (SGT1). In this work, we found that an effector protein named RipAC, secreted by the plant pathogen Ralstonia solanacearum, associates with SGT1 to suppress NLR-mediated SGT1-dependent immune responses, including those triggered by another R. solanacearum effector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 75 publications
2
62
1
Order By: Relevance
“…The strategy of manipulating host protein complexes is also illustrated by the T3SE RipAC from R. solanacearum . This effector inhibits ETI but not cell death caused by general elicitors such as the Phytophthora infestans secreted protein INF1 or the mammalian pro-apoptotic protein Bax, indicating specificity for programmed cell death responses arising from T3SE recognition [ 112 , 113 ]. Interestingly, RipAC contains tandem LRR motifs that are required for ETI suppression, suggesting that it may act as a scaffold for protein–protein interactions.…”
Section: T3ses With Indirect And/or Non-enzymatic Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of manipulating host protein complexes is also illustrated by the T3SE RipAC from R. solanacearum . This effector inhibits ETI but not cell death caused by general elicitors such as the Phytophthora infestans secreted protein INF1 or the mammalian pro-apoptotic protein Bax, indicating specificity for programmed cell death responses arising from T3SE recognition [ 112 , 113 ]. Interestingly, RipAC contains tandem LRR motifs that are required for ETI suppression, suggesting that it may act as a scaffold for protein–protein interactions.…”
Section: T3ses With Indirect And/or Non-enzymatic Mechanisms Of Actionmentioning
confidence: 99%
“…Interestingly, RipAC contains tandem LRR motifs that are required for ETI suppression, suggesting that it may act as a scaffold for protein–protein interactions. Indeed, two independent studies found that RipAC interacts with homologs of SUPPRESSOR OF G2 ALLELE OF skp1 (SGT1), a positive regulator of plant immunity [ 112 , 113 ]. A molecular chaperone complex comprising SGT1, RAR1, and Hsp90 is required for NLR stability and function [ 273 ], and RipAC interferes with the SGT1–RAR1 interaction in an LRR-dependent manner [ 113 ].…”
Section: T3ses With Indirect And/or Non-enzymatic Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify whether RipAC affects PTI in Arabidopsis, we characterized PAMPinduced responses in Arabidopsis transgenic lines overexpressing RipAC (Yu et al, 2020a). Two independent RipAC-GFP overexpression lines showed a decreased ROS burst in response to bacterial or fungal PAMPs (flg22 Pto , elf18 Rsol , and chitin; Figures 1A-C).…”
Section: Ripac Suppresses Pattern-triggered Immunitymentioning
confidence: 99%
“…R. solanacearum relies on a type-III secretion system to deliver over 70 Type-III effector proteins (T3Es) into the host cytoplasm (Sabbagh et al, 2019). One of these T3Es, RipAC, is able to suppress effector-triggered immunity (ETI) by targeting SGT1, and is required for full virulence of R. solanacearum in tomato and Arabidopsis (Yu et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%